La No Aplicación del Sistema de Educación Intercultural Bilingue Atenta la Plurinacionalidad del Estado, Propicia la Globalización Educativa, La Extinción de la Lengua y Cultura Indígena - Arévalo Medina., Julio Cesar (2016)
In the present research work done concerning. "The non-application of the system of bilingual intercultural education attentive plurinationality state fosters educational globalization, the extinction of the indigenous language and culture." We can conclude our research work after making a doctrinaire, normative study showing that educational globalization is a factor that affects the Ecuadorian society causing serious effects such as deterioration of the language of intercultural relations (Kichwa) and indigenous cultural knowledge, since the problem of globalization is that is that if too many barriers set in enterprises, simply they do not enter the country, but if given absolute freedom, end standardizing customs and implemented in our country as education and culture alien people and causing much bigger problems systems as enable the country to develop this is what happens in our country large companies entering make their investments using raw material and personnel from other countries if it does not give any to our benefit, and in turn impart traditions customs different cultures without knowing our having no technology transfer adequate and compete with technologies from foreign tip that will have products with much lower prices and lead to bankruptcy for many domestic companies here should be emphasized that enters competitiveness which Ecuador has no large production companies to be in the process of globalization and that as we see our country is developing and is not in a degree of competitiveness in underdeveloped countries.